Orthodontic Treatment Need and the Psychosocial Impact of Malocclusion in 12-Year-Old Hong Kong Children - Derek Baram; Yanqi Yang; Chong Ren; Ziling Wang; Ricky Wing Kit Wong; Urban Hägg; Colman McGrath; Min Gu (The Scientific World Journal)
Objectives. To determine the prevalence of orthodontic treatment need in 12-year-old children in Hong Kong and its relationship with the psychosocial impact of malocclusion and to assess their associations with sociodemographic factors. Materials and Methods. A random sample of 687 12-year-old children was recruited from 45 secondary schools in Hong Kong. Orthodontic treatment need was assessed on study models by five indices: the Dental Health Component of the Index of Orthodontic Treatment Need (IOTN-DHC), the Aesthetic Component of the IOTN (IOTN-AC), the Dental Aesthetic Index (DAI), the Index of Complexity Outcome and Need (ICON), and the Peer Assessment Rating (PAR). The psychosocial impact of malocclusion on participants and sociodemographic factors were obtained from a questionnaire. Logistic regression was used to examine the correlations between treatment need and the psychosocial impact of malocclusion as well as their associations with sociodemographic factors. Results. The final number of participants was 667 (339 boys and 328 girls, participation rate 667/687 = 97.1%). The prevalence of orthodontic treatment need varied depending on the indices used (10.9–47.8%), but significant correlations were found among the five indices (p < 0.01). The uptake of treatment among the cohort was 2.3%. Boys had higher IOTN-DHC (p < 0.05), DAI (p < 0.05), and PAR (p = 0.05) scores than girls. IOTN-AC was significantly associated with the psychosocial impact of malocclusion (p < 0.05). Parents’ level of education and household income were not significantly associated with either treatment need or the psychosocial impact of malocclusion (p > 0.05). Conclusion. The need for orthodontic treatment in 12-year-old children in Hong Kong remained high, and the uptake of treatment was low. Boys had a higher normative treatment need than girls. Among the five indices, IOTN-AC appears to be the best indicator of the psychosocial impact of malocclusion.